2017
DOI: 10.1080/24750573.2017.1379717
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, validity, and factorial structure of the Turkish version of the Weight Self-Stigma Questionnaire (Turkish WSSQ)

Abstract: OBJECTIVE: The Weight Self-Stigma Questionnaire (WSSQ) is a comprehensive instrument for the assessment of weight self-stigma in obesity and has been validated in several languages. The purpose of this study was to examine the psychometric properties and validate the Turkish version of the WSSQ in a sample of severely obese patients in Turkey. METHODS: A cross-cultural adaptation of the WSSQ into Turkish was carried out, strictly according to recommended methods. The questionnaires including the Sociodemograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 23 publications
5
57
0
Order By: Relevance
“…Across these measures, studies have demonstrated significant correlations between WBI and dietary restraint ( r values = 0.21–0.50), eating concerns ( r values = 0.37–0.64), drive for thinness ( r = 0.47) and measures assessing disinhibition, uncontrolled eating and emotional eating ( r values = 0.46–0.65). Moderate to strong correlations ( r values = 0.29–0.77) were documented for associations between WBI and global or total scores for measures of disordered eating . As with binge eating, measures of eating pathology were associated with WBI in both clinical and community samples and across body weight statuses.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Across these measures, studies have demonstrated significant correlations between WBI and dietary restraint ( r values = 0.21–0.50), eating concerns ( r values = 0.37–0.64), drive for thinness ( r = 0.47) and measures assessing disinhibition, uncontrolled eating and emotional eating ( r values = 0.46–0.65). Moderate to strong correlations ( r values = 0.29–0.77) were documented for associations between WBI and global or total scores for measures of disordered eating . As with binge eating, measures of eating pathology were associated with WBI in both clinical and community samples and across body weight statuses.…”
Section: Resultsmentioning
confidence: 94%
“…Importantly, several studies found that WBI predicted anxiety over and beyond the variance accounted for by participants' BMI . Of note, half of the current studies examining links between WBI and anxiety were conducted outside of North America, in Australia , Germany , Spain , Sweden and Turkey .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations